Seawater pretreatment by dissolved air flotation filtration in reverse osmosis desalination - Chui, Peng Cheong. (2009)
A pilot desalination plant using reverse osmosis (RO) membrane technology was set up in Tuas South, Singapore, by M/S Hyflux Pte Ltd to conduct treatability studies for a proposed RO desalination plant. The feasibility of seawater desalination using RO membrane was investigated through measurements of field data pertaining to local seawater properties and plant system operating parameters. Upon completion, the proposed desalination plant will provide the Public Utilities Board (PUB) with a daily supply of 136,380 m3 of desalinated water, which is about 10% of Singapore’s water demand (Hyflux Group Website: http://www.hyflux.com/; Singapore Public Utilities Board Website: http://www.pub.gov.sg/). A Memorandum of Understanding (MOU) was signed on the 14th of October, 2003 between Hyflux and the Nanyang Technological University (NTU) for research collaborations in the water membrane area. In this project, NTU was granted access to Hyflux’s pilot desalination plant to conduct evaluation and optimization experiments on the different operation stages of the sea water desalination process. Hyflux would also share other results of evaluation and optimization of the different stages with NTU. Several pretreatment processes such as dissolved air flotation filtration (DAFF) and ultra-filtration (UF) using membranes were evaluated in the pilot desalination plant over a one year period. Both processes were applied prior to the RO membrane desalination process to treat raw seawater to a turbidity of less than 0.1 NTU, and a silt density index (SDI) of less than 3. In the DAFF system, the clarification and filtration processes are combined as one unit, making the pretreatment system a compact one. It is capable of removing color, and suspended and colloidal solids through the process train comprising coagulation-flocculation, dissolved air floatation (DAF) clarification and sand filtration.